Comparison of mortality between early and late tracheostomy in patients hospitalized by COVID-19 in an intensive care unit (Research, Society and Development, 2023)
Introduction: COVID-19 is an acute respiratory infection caused by the SARS-CoV-2 coronavirus, potentially serious, highly transmissible and globally distributed. Objective: to analyze the impact of early and late tracheostomy (TQT) in patients with COVID-19 on the type of ventilatory weaning and mortality. Methodology: This study will be a retrospective observational cohort, evaluating patients diagnosed with COVID-19 admitted to an Intensive Care Unit (ICU) of a tertiary center in the city of Aracaju, SE, from November 2020 to July 2020. 2021. The collection will be guided by a structured collection form with variables of interest. The primary outcome will be the in-hospital mortality within 60 days, from the date of the TQT performance, compared between patients who were tracheostomized early and those who were late. Results: A total of 197 patients were admitted to the ICU, but only 72 were eligible for inclusion in the study. The “early TQT” group had less time on ventilator, as well as ICU stay, but no difference was found between the time from performing the procedure until the occurrence of the outcome. Conclusion: After a thorough analysis of the data, it is suggested that the process of hospitalization in the ICU and COVID-19 increased the need for the tracheostomy procedure, but the study was not significant when we compared the mortality outcome in the group that performed it early or late the procedure.